La Cause a-t-elle réellement disparu du Droit français des Contrats? - Deshayes, Olivier; Genicon, Thomas; Laithier, Yves-Marie (European Review of Contract Law, 2017)
Has French law abandoned the concept of « cause » ? That is the impression one might have on reading the new provisions of the Civil Code, introduced by the Ordonnance of 10 February 2016, and certain commentaries. Accused of being a source of deviance and misunderstanding, the « cause » had to be eradicated, it was said, so that clarity, security and attractiveness of the Code be restored. A closer look, however, shows how far from reality this much-told fable actually is. Two sets of factors bear witness to the perennity of the « cause » in the new law. Firstly, the vast majority of previous « cause »-based solutions are taken up by new provisions. The « cause » remains but its presence is masked by a new designation (« motive » or « purpose », for example). Secondly, there are situations where, in a quest for coherence or in order to fill a gap, a « cause »-based reasoning will prevail exactly as it did before the reform. When all is said and done, it is a strange reform that removes the name while allowing the substance to remain.